Assessing the Quality of Community-Based Health Services: A Case Study of Integrated Health Posts in Rural Indonesia - Buamona, Seli; Ohoiwutun, Stanislaus Kostka; Salampessy, Maryam (Pattimura University, 2026)
Community-based health services play a crucial role in improving maternal and child health outcomes, particularly in rural areas of developing countries. In Indonesia, Integrated Health Posts (Posyandu) serve as a primary platform for delivering basic health services through community participation. However, disparities in service quality remain a major challenge, especially in remote villages. This study aims to analyze the quality of health services provided by Posyandu in Umaloya Village, Sanana District, Sula Islands Regency, Indonesia. Using a qualitative descriptive approach, data were collected through in-depth interviews, direct observation, and documentation involving health workers, Posyandu cadres, community leaders, and service users. The analysis is guided by the SERVQUAL framework, which includes five dimensions of service quality: tangibles, reliability, responsiveness, assurance, and empathy. The findings reveal that while Posyandu services in Umaloya Village are generally accessible and supported by strong community involvement, several limitations persist. These include inadequate health facilities, limited cadre training, and low community awareness regarding the importance of routine maternal and child health services. Among the SERVQUAL dimensions, empathy and responsiveness were relatively well perceived, whereas tangibles and reliability showed significant weaknesses. The study highlights the importance of strengthening human resources, improving infrastructure, and enhancing community education to ensure sustainable and high-quality health services. The findings contribute to the literature on public health service quality in rural settings and provide practical recommendations for policymakers and local health authorities to improve the performance of community-based health programs.